Thonningianin A ameliorated renal interstitial fibrosis in diabetic nephropathy mice by modulating gut microbiota dysbiosis and repressing inflammation - Zhang, Shujiao; Zhang, Shuaixing; Bai, Xuehui; Wang, Yaoxian; Liu, Yuning; Liu, Weijing (Frontiers in Pharmacology, 2024)
This study was conducted to examine the potential health benefits of thonningianin A (TA) on renal injury and interstitial fibrosis in diabetic nephropathy(DN) mice.In this study, a DN mice model was established using male C57BL/6 mice injected with streptozotocin(STZ, 50 mg/kg) intraperitoneally and treated with TA for 12 weeks. Firstly, the therapeutic and anti-fibrotic effects of TA on DN were evaluated. Secondly, the effect of TA on renal inflammation was evaluated and western blot was used to detect the changes of NLRP3/ASC/Caspase-1 pathway-related protein expressions in kidney. Furthermore, the effect of TA on impairments in the intestinal mucosa barrier was evaluated and the changes of lipopolysaccharide (LPS) levels in feces and serum were detected by ELISA. Finally, 16S rRNA sequencing was used to detect alteration of gut microbiota diversity and abundance in mice after TA treatment.The results showed that TA markedly mitigated blood glucose(Glu), decreased 24-hour urinary total protein(24hUTP), improved renal dysfunction and kidney index(KI) in DN mice. Furthermore, TA significantly alleviated renal injury and interstitial fibrosis, repressing renal inflammation. Western blot results showed that the NLRP3/ASC/Caspase-1 signaling pathwayrelated proteins decreased after TA treatment. In addition, TA also ameliorated impairments in the intestinal mucosa barrier and restored the expressions of intestinal tight junction proteins(Claudin-1, Occludin and ZO-1). Subsequently, it reduced LPS levels of DN mice in fecal and serum.Furthermore, 16S rRNA high-throughput sequencing showed that TA modulated gut microbiota dysbiosis and decreased the abundance of Gram-negative bacteria (Proteobacteria and Escherichia-Shigella).Conclusions: This study suggested that TA might exert a beneficial effect on renal interstitial fibrosis in DN mice by modulating gut microbiota dysbiosis, ameliorating impairments in the intestinal mucosa barrier, reducing the production and release of LPS, inhibiting the activation of NLRP3/ASC/Caspase-1 signaling pathway, and repressing renal inflammatory.